Meningkatkan Hasil Belajar Fisika Materi Usaha Dan Energi Melalui Penerapan Model Pembelajaran Thinking Aloud Pair Problem Solving (TAPPS) Pada Siswa Kelas X MIPA. 1 SMA Negeri 5 Palu - Abd. Razak (Politeknik Negeri Samarinda, 2022)
Physics learning at SMA Negeri 5 Palu is generally dominated by teachers, causing low student learning outcomes. The purpose of this study was to improve the learning outcomes of physics on work and energy through the application of the Thinking Aloud Pair Problem Solving (TAPPS) learning model for class X MIPA students. 1. This research is a class action research (CAR) in class X MIPA students. 1 SMA Negeri 5 Palu with a total of 33 students. This classroom action research was conducted in two cycles with material on work and energy. In this study, data were collected through observation sheets from teacher activities in managing the TAPPS learning model and student activities, as well as tests of the results of each cycle's actions. From the results of the study showed that the activities of teachers and students experienced an increase from cycle I to cycle II and were in the very good and very good categories. Based on the analysis of learning outcomes, it was obtained that student data from cycle I to cycle II increased, where the classical absorption value of cycle I was 66.88%, and cycle II was 79.19%, an increase of 12.31%. For classical learning mastery it increased by 21.21% with the classical mastery value of cycle I was 60.61% and cycle II was 81.82%. Based on the indicators of the success of this study, namely if the percentage of classical absorption was 80% and classical completeness was 80%, it was concluded that the application of the TAPPS learning model could improve the learning outcomes of physics on work and energy in class X MIPA students. 1 SMA Negeri 5 Palu.